Regulatory mechanisms of growth hormone secretion are sexually dimorphic. - Jaffe, C A (1998)
Sexually dimorphic growth hormone (GH) secretory pattern is important in the determination of gender-specific patterns of growth and metabolism in rats. Whether GH secretion in humans is also sexually dimorphic and the neuroendocrine mechanisms governing this potential difference are not fully established. We have compared pulsatile GH secretion profiles in young men and women in the baseline state and during a continuous intravenous infusion of recombinant human insulin-like growth factor I (rhIGF-I). During the baseline study, men had large nocturnal GH pulses and relatively small pulses during the rest of the day. In contrast, women had more continuous GH secretion and more frequent GH pulses that were of more uniform size. The infusion of rhIGF-I (10 microg/kg/h) potently suppressed both spontaneous and growth hormone-releasing hormone (GHRH)-induced GH secretion in men. In women, however, rhIGF-I had less effect on pulsatile GH secretion and did not suppress the GH response to GHRH. These data demonstrate the existence of sexual dimorphism in the regulatory mechanisms involved in GH secretion in humans. The persistence of GH responses to GHRH in women suggests that negative feedback by IGF-I might be expressed, in part, through suppression of hypothalamic GHRH.